Les forêts ripariennes du Québec - Rousseau, Jacques (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1962)
Contrary to a popular belief, the forest is not always strictly a land habitat. The fact is well known for the Souther regions, from the Dismal Swamp of Georgia to tropical mangroves. In Northeastern America, in the temperate zone, semi-aquatic forests are also found, one type being the riparian forest of the fresh water shores of the upper St. Lawrence Valley. During the spring the surface is normally flooded, but in summer it free from water. These forests are summarily described in the accompanying paper, in relation to the normal high water level and to the river bed. In the past, these areas were hardly used, but they could support a profitable horticultural development, provided that a special technique is used, as in the case of the Dutch polder or the hortillonnageof the Amiens region.